(untitled) (Al-Academy, 2026)
Contemporary Saudi art is witnessing numerous intellectual, social, and cultural transformations, resulting in a diversification in the use of modern technologies, thus enhancing the viewer’s visual experience. This research seeks to study the aesthetics of digital storytelling in virtual reality within contemporary Saudi art. The research aims to define the concept of virtual reality, clarify the concept of digital storytelling, and analyze some contemporary artworks that rely on digital storytelling to reveal the aesthetics achieved by virtual reality in contemporary Saudi art. The importance of this research lies in enriching the digital library with studies that link digital storytelling and virtual reality, and in supporting the Kingdom’s Vision 2030 strategy for digital transformation. This study may theoretically be useful in revealing the most important virtual reality software in the field of contemporary art. The research followed a descriptive-analytical approach, and the research sample consisted of analyzing two contemporary Saudi artworks from 2022. The research reached a number of conclusions, The emergence of a set of aesthetics in digital storytelling, including digital aesthetics, exclusivity to digital accounts, interaction, immersion, non-linear plot, geometric first, line and line, the aesthetics of auditory addiction, the aesthetics of excitement and language. Virtual reality technology was researched in daily digital storytelling in events, in the role of the recipient from a passive role to an active role in the experience. The method of displaying artworks in contemporary Saudi art was chosen from exhibitions to adventure. The date of its environment and heritage was chosen because it is its history in the field of contemporary arts. Thus, the research results reached several experts, including: distinguishing the study by the cooperation of artists and programmers collaborating to create in the field of realistic experiences